Achieving Success Through Innovation : Cases and Insights from the Hospitality, Travel, and Tourism Industry. - Verma, Rohit (Service systems and innovations in business and society collection., 2016)
This book investigates the genesis and success of innovation in the hospitality industry as detailed in over four dozen case studies. In many of the cases, the innovators themselves provide the insights into their innovative inspiration and the lessons learned from the way they brought their ideas to life. The cases include innovations for improved customer service, stronger human resources, and new food service and lodging concepts. While updated technology forms the basis for many of the innovations, some of the cases focus specifically on technology improvements, with a particular focus on the use of technology as a mediator in the service value chain. With the passage of several years, the book shares the outcome of the innovative concepts--most of which continue to operate. The lessons presented will provide you a valuable perspective on success through innovation, whether you are operating in the hospitality industry or another business.